Judicial Fallibility, Inverted Learning and the Indispensability of Reason: Piloting 'Advanced Legal Reasoning' in Ireland. (January 2019) - Cahill, Maria
In many law schools around the world, the Socratic method is a cultural anathema and the Oxbridge tutorial system a financial impracticability: how then can these law schools, which adhere to the traditional lecture format nonetheless promote the dedicated teaching of legal reasoning? Seven years ago, a specific module dedicated to the development of these skills, Advanced Legal Reasoning, was offered for the first time as an optional final-year module at University College Cork in Ireland. This course probes the requirements of legal reasoning in the context of particular cases, and it proposes a modified version of the 'flipped classroom' phenomenon, an approach called Inverted Learning, to do so. This article proposes four principles of Inverted Learning, which are (a) first exposure responsibility, (b) support for experimentation, (c) expectation of mastery and (d) humanization of the classroom. They inculcate the virtues of intellectual autonomy, intellectual courage, intellectual humility and intellectual charity, respectively. Each of these principles was put into practice in very concrete ways through the delivery of the Advanced Legal Reasoning module in order to develop the capacity of the students to reason effectively and to appreciate the indispensability of reason within the legal system.